(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
The text addresses the partnership between Bruno Beltrão’s Street Dance and Pop Philosophy, highlighting the 18-month experience of collaboration between urban dance and pop philosophy. The author explores the use of materials derived from popular culture, such as art, science, and sports videos, to explore themes and questions of philosophy. The text also mentions the theoretical and practical repercussions of the interactions between dance and philosophy, with the conceptual rehabilitation of the street as a guiding thread.